Security dimension of european integration in the context of changing international system - Aka, Halit Burç (My University, 2009)
Key Words: European Union, International Relations Theory, Security, EU Integration ABSTRACT This study seeks to elucidate to what extent the general security understandings which have come to the forefront work in conjunction with the changes which have occurred in the international system since World War II and up to the present; how have these changes influenced the security dimension of European integration. In order to realize this goal, the security understandings dominating the international system since the World War II are explained. Later the security understanding coming forth in the international system is measured in the context of European integration. This study allows both the large picture (the security concept of the international system) and the small picture (the security approach of the European integration) to be compared. Avrupa Birliği, Uluslararası İlişkiler Teorileri, Güvenlik, AB Bütünleşmesi

Bu çalışmanın amacı, ikinci dünya savaşından günümüze kadar uluslararası sistemde meydana gelen değişimlere bağlı olarak öne çıkan genel güvenlik anlayışlarının, Avrupa bütünleşmesinin güvenlik boyutunu ne ölçüde etkilediğini ortaya koymaktır. Amacı gerçekleştirmek için, öncelikle ikinci dünya savaşından itibaren uluslararası sisteme hakim olan güvenlik anlayışları tespit edilir. Sonrasında, uluslararası sistemde öne çıkan güvenlik anlayışı, Avrupa bütünleşmesi alt sisteminde test edilir. Kısacası, çalışmada büyük fotoğrafla (uluslararası sistemin güvenlik anlayışı) küçük fotoğraf (Avrupa bütünleşmesinin güvenlik anlayışı) karşılaştırılmaktadır.
Keywords: Avrupa Birliği Entegrasyon; Güvenlik_Avrupa Birliği; Uluslararası İlişkiler